Biodentine ®: a new option for the treatment of furcal perforation - Takuma-Shinkawa, Arturo (2018)
Endodontic therapy is not free from complications such as perforations at different levels, with furcation associated with cameral opening; however, the use of Bioceramic cements at present allows predictable results. We present a case of a lower left first molar with asymptomatic irreversible pulpitis and apical periodontitis with the complication of perforation of the chamber floor, sealing it after the end of the root canal treatment with Biodentine TM.